2011
DOI: 10.1111/j.1465-7287.2010.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Glass Ceiling: Slow Progress Ahead

Abstract: Studies show that the percentage of female senior managers in large corporations continues to grow slowly. I consider a firm that initially has an entirely male management structure. If this firm suddenly shifts its behavior and begins to hire male and female managers in equal numbers and treats them equally, then the gender composition of the firm's managers will change over time. Using well-established mathematical methods, I derive equations that show how rapidly this change will occur. Using data from prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
4
1
Order By: Relevance
“…The results also show geographic disparities, which were also noticed in the overall private sector (Chanavat 2012). When compared to the 2003 study, showing that only 3-5% of the top positions were occupied by women in the United States (Goodman et al, 2003), the results of the research show a slightly better situation in the private equity sector, potentially due to a trend of an increased number of females in the top management (Fain, 2011). Furthermore, the results of the study support the research showing that female executives tend to work in high risk industries (Paul & Sahni, 2009).…”
Section: Resultscontrasting
confidence: 55%
“…The results also show geographic disparities, which were also noticed in the overall private sector (Chanavat 2012). When compared to the 2003 study, showing that only 3-5% of the top positions were occupied by women in the United States (Goodman et al, 2003), the results of the research show a slightly better situation in the private equity sector, potentially due to a trend of an increased number of females in the top management (Fain, 2011). Furthermore, the results of the study support the research showing that female executives tend to work in high risk industries (Paul & Sahni, 2009).…”
Section: Resultscontrasting
confidence: 55%
“…The most frequent external variables identified in the literature include lack of mentoring and sponsorship (Hom et al, 2008;Meyers, 2015;McDonald and Westphal, 2013), exclusion from informal networks (Cook and Glass, 2014;Fain, 2011;Kulich et al, 2015), lack of flexibility (Klettner et al, 2016;Waumsley and Houston, 2009;Williams et al, 2013), motherhood penalties (Budig et al, 2012;Kmec et al, 2014;Kricheli-Katz, 2012;Stone and Hernandez, 2013), gender stereotyping (Burke and Major, 2014;Branson et al, 2013;Heilman, 2001), the male-centered work ethos (Cahusac and Kanji, 2014;Cabrera, 2009;Kelly et al, 2010;Widera et al, 2010) and the glass ceiling (Cook and Glass, 2014;Fain, 2011;Kulich et al, 2015;Sabharwal, 2013).…”
Section: Push and Pull Variablesmentioning
confidence: 99%
“…Progress towards gender equality in leadership in the last decade has been slow. Fain (2011) concluded that achieving equality in lower positions on the scale takes less time than in positions of greater responsibility. In the latter case, equality could take up to 60 years.…”
Section: Women and The Gc: Present Situation And Future Prospectsmentioning
confidence: 99%